2018
DOI: 10.1200/jgo.17.00061
|View full text |Cite
|
Sign up to set email alerts
|

In Their Own Words: A Qualitative Study of Kenyan Breast Cancer Survivors’ Knowledge, Experiences, and Attitudes Regarding Breast Cancer Genetics

Abstract: IntroductionBreast cancer ranks among the most common adult cancers in Kenya. Individuals with a family history of the disease are at increased risk. Mutations most commonly associated with breast cancer affect BRCA1 and BRCA2; mutations in several other genes may also confer breast cancer risk. Genetic testing and counseling can help patients understand their risk and assist clinicians in choosing therapies. We aimed to uncover what patients know, experience, and think with regard to breast cancer genetics in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…This study was carried out in Nairobi and its environs where most of the cancer care services in Kenya are found and may therefore not be generalizable. However, we were able to gather information on BCC that is similar to other studies carried out in Kenya and other SSA countries . Women's views on aspects of BCC and their recommendations are considered and presented in Table with expected outcomes.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This study was carried out in Nairobi and its environs where most of the cancer care services in Kenya are found and may therefore not be generalizable. However, we were able to gather information on BCC that is similar to other studies carried out in Kenya and other SSA countries . Women's views on aspects of BCC and their recommendations are considered and presented in Table with expected outcomes.…”
Section: Discussionmentioning
confidence: 97%
“…Although several studies in sub‐Saharan Africa (SSA), including Kenya, have identified barriers and facilitators to early detection, diagnosis, and treatment, it is not clear if the list is exhaustive. Barriers identified include low or lack of BC awareness, partner consensus, lack of information, distant health facilities, long queues in hospitals, costs, fear, stigma, and inadequate health professionals to perform tests or to provide genetic counseling . Facilitators are educational messages and social support from religious persons and partners .…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge about genetic testing and counseling appears to be generally poor in various surveyed populations (Hall et al, ; Lipkus, Iden, Terrenoire, & Feaganes, ; Sheppard et al, ). Higher education levels in a sample from Austria (Staudigl et al, ), prior history of BC in a sample of African‐American women (Sheppard et al, ), and a family history of BC (Lipkus et al, ; MacNew, Rudolph, Brower, Beck, & Meister, ) appeared to impact the level of knowledge, although this was not the case in other studies (Hall et al, ; Lee et al, ). In our sample, only 16.0% knew about genetic testing.…”
Section: Discussionmentioning
confidence: 93%
“…Patients and their families were integral members of the strategy, which also included clinicians, community health workers, and policy makers [17]. By sharing their experiences and views through annual KNRbS meetings and working groups, patients contributed to the design and development of retinoblastoma awareness campaigns and healthcare delivery centered on retinoblastoma genetics [18,19] and histopathology services [20]. Since the initiation of KNRbS, the age at diagnosis for patients with bilateral retinoblastoma has decreased from 24.4 to 16.8 months of age, and for unilateral patients from 35.9 to 24 months of age, figures more comparable to those observed in HICs and linked to better survival [21].…”
Section: Case Study: Patient Engagement In Retinoblastoma Researchmentioning
confidence: 99%
“…Patients with cancer report experiencing social stigma, with consequences such as termination of employment, familial shame, and social rejection [23,31,33]. In some regions, beliefs persist that cancer is caused by witchcraft and, therefore, patients prefer to keep their disease private [19]. Additionally, some patients experience feelings of defeat and fatalistic attitudes when describing their experiences with cancer, many of whom ignored early signs of their cancer and/or delayed care as a result of misconceptions of cancer as incurable [32].…”
Section: Cultural Stigmamentioning
confidence: 99%